2021
DOI: 10.1128/msphere.01156-20
|View full text |Cite
|
Sign up to set email alerts
|

OXA-181-Like Carbapenemases in Klebsiella pneumoniae ST14, ST15, ST23, ST48, and ST231 from Septicemic Neonates: Coexistence with NDM-5, Resistome, Transmissibility, and Genome Diversity

Abstract: Studies on the epidemiology and genomes of isolates harboring OXA-48-like genes in septicemic neonates are rare. Here, isolates producing these carbapenemases which emerged and persisted in an Indian neonatal unit were characterized in terms of their resistome, transmissibility, and genome diversity. Antibiotic susceptibility and whole-genome sequencing were carried out. The sequence types, resistome, virulome, mobile genetic elements, and transmissibility of carbapenem-resistant plasmids were evaluated. Core … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 46 publications
6
20
0
Order By: Relevance
“…Numerous high-risk K. pneumoniae clones, among them ST14, have now been identified [2]. ST14 strains have been reported to produce a wide range of carbapenemases: apart from being the sequence type from which the bla NDM-1 gene was first identified [18], various bla KPC [9,19,20], bla NDM [21,22], and bla OXA-48-like [6,[23][24][25][26] alleles or double carbapenemase producers have been reported from different parts of the world, including the Middle East [7,8,[27][28][29][30][31]. Furthermore, ST14 strains appear to be one of the most wide-spread, highly resistant CRE clones in Dubai [8].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous high-risk K. pneumoniae clones, among them ST14, have now been identified [2]. ST14 strains have been reported to produce a wide range of carbapenemases: apart from being the sequence type from which the bla NDM-1 gene was first identified [18], various bla KPC [9,19,20], bla NDM [21,22], and bla OXA-48-like [6,[23][24][25][26] alleles or double carbapenemase producers have been reported from different parts of the world, including the Middle East [7,8,[27][28][29][30][31]. Furthermore, ST14 strains appear to be one of the most wide-spread, highly resistant CRE clones in Dubai [8].…”
Section: Discussionmentioning
confidence: 99%
“…By feature selection, we proposed a top 40 feature-based regression model, which had the best predictive performance of 91%. First, according to Naha et al (2021) and Okanda et al (2020), we found that gene mutations may affect drug resistance of Klebsiella; thus, we tried to find the relevant sites affecting resistance by calling SNPs. After pre-processing the raw data by using biogenetics tools BWA, BCFTools, and SamTools, we obtained a matrix of mutation site and sample list.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that earlier studies reported the presence of a single carbapenemase in K. pneumoniae but in recent years reports of co-occurrence of multiple carbapenemases are emerging (16,75,82). In a recent study from India OXA-181/OXA-232 was concomitantly present with NDM-5 in K. pneumoniae causing neonatal septicemia (82).…”
Section: Drug-resistant Bug and The Newbornmentioning
confidence: 98%